Exploring Gastrointestinal Health in Diabetic Cats: Insights from Owner Surveys, Ultrasound, and Histopathological Analysis - Marisa Esteves-Monteiro; Cláudia S. Baptista; Diogo Cardoso-Coutinho; Clara Landolt; Patrícia Dias-Pereira; Margarida Duarte-Araújo (Veterinary Sciences)
Diabetes is a metabolic disorder characterized by chronic hyperglycemia, affecting between 0.21% and 1.24% of cats. While gastrointestinal complications are well-documented in human diabetic patients—affecting up to 75%—similar data in cats remain scarce. This study explores gastrointestinal alterations in diabetic cats using ultrasound and histopathological evaluations, alongside assessing owners’ perceptions of digestive issues. A brief survey was conducted with the owners of diabetic cats to document diabetes symptoms and any gastrointestinal changes. Following the survey, each cat underwent abdominal US, focusing on the digestive tract including the stomach, duodenum, jejunum, ileum, and colon. Additionally, histopathological analysis was conducted on necropsied diabetic cats. Thirteen domestic spayed diabetic cats with no prior gastrointestinal disease were included, with 83% showing at least one gastrointestinal issue reported by owners. All cats exhibited increased gastric, duodenal, and jejunal wall thickness, while the ileum and colon showed normal thickness. Histopathological evaluation revealed increased thickness of the muscular layers, inflammatory infiltrate, and collagen deposits in the whole length of the gastrointestinal tract. These findings suggest that diabetic cats may experience gastrointestinal remodeling, a phenomenon that, while well recognized in human diabetes, has not been adequately studied in feline patients.